Tehran children : a Holocaust refugee odyssey - Dekel, Mikhal, 1965- (W.W. Norton & Company, Inc., 2019)
"The extraordinary true story of Polish-Jewish child refugees who escaped the Nazis and found refuge in Iran. More than a million Jews escaped east from Nazi occupied Poland to Soviet occupied Poland. There they suffered extreme deprivation in Siberian gulags and "Special Settlements" and then, once "liberated," journeyed to the Soviet Central Asian Republics. The majority of Polish Jews who survived the Nazis outlived the war in Uzbekistan and Kazakhstan; some of them continued on to Iran. The story of their suffering, both those who died and those who survived, has rarely been told. Following the footsteps of her father, one of a thousand refugee children who traveled to Iran and later to Palestine, Dekel fuses memoir with historical investigation in this account of the all-but-unknown Jewish refuge in Muslim lands. Along the way, Dekel reveals the complex global politics behind this journey, discusses refugee aid and hospitality, and traces the making of collective identities that have shaped the postwar world--the histories nations tell and those they forget"--